Volatility Estimation in the Dhaka Stock Exchange (DSE) returns by Garch Models - Aziz, Md. Shawkatul Islam; Uddin, Md. Nezum (Asian Business Review, 2014)
This study aimed at understanding the volatility of Dhaka Stock Exchange (DSE). The daily and monthly average DSE General Index (DGEN), from the period January 1, 2002 to July 31, 2013 has been used. The study has been made by using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) models to estimate the presence of volatility. Though volatility is a common phenomenon in the capital market, the study recommends careful monitoring of volatility by the concerned authority if necessary. It is also recommended that activities of corporate insiders should be properly checked and information should become available for all of the interested investors and to ensure adequate supply of stock through active participation of the government and giant national and multinational companies and so forth.
Keywords: ARCH; DSE; GARCH; Stock Market; Volatility